HUBUNGAN PENGETAHUAN DENGAN PERSEPSI GURU SEKOLAH DASAR MENGENAI PENDIDIKAN SEKS DI KECAMATAN KADIPATEN - Nida Nur Majidah Santoso; Diah Gusrayani; Julia (EDU RESEARCH, 2024)
Sex education in schools is aimed to help children to understand everything related to sexuality within themselves, so that they can live their social life in the right way and in accordance with science. Sex education is not a taboo, it is as important as other lessons that should be given especially to elementary school children. This research aims to determine the relationship between knowledge and perceptions of elementary school teachers regarding sex education in Kadipaten District.The population in this research were all elementary school teachers in Kadipaten District, with a total of 190 respondents. The sampling technique used was purposive sampling technique, the final sample used amounted to 112 respondents. This technique was chosen by considering certain criteria relevant to the research objectives. Data collection was conducted through questionnaires covering aspects of everyone's rights, gender equality, sexual and reproductive health, sexual violence, sexual behavior, community habits, experience of sexuality education, perceptions and knowledge of teachers regarding sexuality education. The results obtained from this study indicate that there is a significant negative relationship between the knowledge and perceptions of elementary school teachers regarding sex education in Kadipaten District. Although the majority of teachers had good knowledge and 78.2% of respondents reported learning sex education at school, challenges in its implementation remain. This is mainly related to the existing social and cultural norms in the community, where sex education is often considered taboo or sensitive. Gender stereotypes and lack of support from parents and communities are also factors that affect the effectiveness of teaching sex education. Thus, it is important to overcome these barriers so that sex education can be effectively implemented in the basic education curriculum.